2021
DOI: 10.3389/fpls.2021.649684
|View full text |Cite
|
Sign up to set email alerts
|

No Tillage With Plastic Re-mulching Maintains High Maize Productivity via Regulating Hydrothermal Effects in an Arid Region

Abstract: Plastic is a valuable mulching measure for increasing crop productivity in arid environments; however, little is known about the main mechanism by which this valuable technology actuates spatial–temporal changes in soil hydrothermal effect. So a 3-year field experiment was conducted to optimize soil hydrothermal effect of maize field with three plastic mulched management treatments: (1) no tillage with plastic re-mulching (NM), (2) reduced tillage with plastic mulching (RM), and (3) conventional tillage with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The study observed soil water content levels reaching up to 40% in the 0-10 cm layer and up to 31% in the 10-20 cm layer [22]. This consistency in results affirms that plastic mulching effectively mitigates soil water evaporation and augments soil water retention in the upper layers, not only in an Asian context [3,16,23,24] but also in the highlands of the Andean region.…”
Section: Discussionmentioning
confidence: 60%
“…The study observed soil water content levels reaching up to 40% in the 0-10 cm layer and up to 31% in the 10-20 cm layer [22]. This consistency in results affirms that plastic mulching effectively mitigates soil water evaporation and augments soil water retention in the upper layers, not only in an Asian context [3,16,23,24] but also in the highlands of the Andean region.…”
Section: Discussionmentioning
confidence: 60%
“…To make full use of limited rainfall resources, surface mulching has become an effective measure to increase yield in dry farming agroecosystems. Among the mulching methods, plastic film mulching has been widely used in the agricultural production of arid and semi-arid regions and has demonstrated yield-increasing effects [4][5][6][7][8]. Especially after whole plastic film mulching is adopted, a closed physical barrier is formed on the surface Water 2022, 14, 1894 2 of 13 that effectively reduces soil evaporation and noticeably enhances crop yield and water-use efficiency (WUE) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the Hexi Corridor of northwestern China, a waterlimiting area, no-till is widely adopted to conserve soil water (Yin et al, 2021). Wheat (Triticum aestivum L.) and maize (Zea mays L.) are the two main crop species cultivated in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the wheat received no-till with previous plastic film mulching. It is beneficial for wheat to increase N productivity, as no-till and plastic film mulching can improve soil water status (Yin et al, 2021), and improved water conditions may increase N translocation (NT) (Mon et al, 2016). Moreover, N fertilizer is typically applied to increase N uptake (Tan et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%